Body composition impacts jump performance in D1 athletes - Kramarenko, V.; Bernhardt, V.; Oldham, M. D.; Jones, B.; Bakcha, O.; Byun, C.; Martinez, C.; McClain, J.; Tousant, M. (International Journal of Exercise Science Conference Proceedings, 2025)
INTRODUCTION: Body composition is critical in athletic performance, influencing metrics such as jump height and force production. Variations in body composition, such as increased lean tissue mass and reduced fat mass, have been identified as strong predictors of superior jump performance due to their positive effects on power-to-weight ratios and reduced injury risk (MacDonald et al., 2013). Lean mass is strongly correlated with improved jump performance, as greater lean mass enhances muscle cross-sectional area and, consequently, the force and power generated during physical activities like countermovement jumps (CMJ) (Stephenson et al., 2015). Low body fat percentages are generally associated with higher agility, power, and vertical jump height, making them desirable characteristics in volleyball athletes. (Acar & Eler, 2019).